Implementasi Manajemen Risiko Likuiditas Syariah untuk Menjaga Stabilitas Dana Pihak Ketiga (DPK) - Gusti Oka Widana; Achmad Nazhorie (ITB AAS INDONESIA Surakarta, 2025)
The continuity of Islamic banking activities (BUS) is largely determined by the success of the collection of Third Party Funds (DPK) (Fitriani & Azizoma, 2022; Parenrengi & Hendratni, 2018; Utami, 2023). In addition to indicating the level of public trust (Jyana & Affandi, 2019; Wati & Fasa, 2024), deposits are a vital factor in boosting bank profitability (ROA) (Parenrengi & Hendratni, 2018; Saputri & Nursamsiyah, 2025; Sriyono, Dewi, Hidayati, & Maulida, 2023). However, banking institutions face the threat of Liquidity Risk which is very critical (Nelly, Siregar, & Sugianto, 2022). This risk arises due to the bank's inability to pay off all its financial obligations that have matured (Handayani, 2017; Nelly, Siregar, & Sugianto, 2022), thus being considered a serious threat that triggers bankruptcy (